Comparative effectiveness of S-adenosylmethionine and etoricoxib in newly diagnosed patients of knee osteoarthritis - Chaudhary, Prashant S.; Deshmukh, Shweta V.; Jaybhaye, Deepali L.; Johar, Sukhmeen K.; Pandey, Bajrang L.; Sharma, Gagan A. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Knee osteoarthritis is an important cause for morbidity in elderly people. Therapy is largely symptomatic with nonsteroidal anti-inflammatory drugs which pose risk in the elderly. Methionine is natural body constituent with novel property of blunting S-adenosylmethionine (SAMe) inflammatory process and cartilage degradation. The aim of this study was to compare effectiveness of SAMe, with standard etoricoxib therapy in newly diagnosed knee osteoarthritis cases. Methods: 127 newly diagnosed knee osteoarthritis patients were randomized into two groups. 55 participants received treatment of etoricoxib 600 mg extended release once daily for 90 days (group 1) and 72 received etoricoxib 600 mg extended release once daily and SAMe 400 mg twice daily for initial 15 days followed by SAMe once daily 400 mg as maintenance dose for next 75 days (group 2). The outcomes were measured by knee injury and osteoarthritis outcome score (KOOS). Pre and post treatment KOOS scores of all cases were separately pooled to define the median for whole as well as components of KOOS parameters. Relative frequencies of cases with values around respective medians were compared by MOODS median test. Patient characteristics, disease characteristics were also examined for bearing on outcomes besides the treatment. Results: SAMe treatment was associated with significantly greater improvement in symptoms, activities of daily life, spontaneous recreational activities and the quality of life compared to etoricoxib therapy. The therapy was well-tolerated. Conclusions: The study confirms SAMe as superior therapeutic option in osteoarthritis. SAMe indeed has been reported to have specific anti-arthritic effects and promotive to general well-being.